HUBUNGAN KEBIASAAN SARAPAN DENGAN PRESTASI BELAJAR SISWA SEKOLAH DASAR NEGERI 13 KABILA KECAMATAN KABILA KABUPATEN BONE BOLANGO - Anasiru, M. Anas; Misnati, Misnati; Puspawati, Ni Nengah (Jurusan Gizi Politeknik Kesehatan Gorontalo, 2017)
ABSTRACT Learning achievement is the mastery of knowledge or skills developed through the subjects, embodied in the form of values or numbers. Learning achievement that is displayed with the scores or numbers created by teachers based on assessment guidelines on each student is different, based on the level of mastery of the competencies that have been set. The problem studied is whether breakfast has an influence on student achievement in school. This study aims to determine the relationship between Breakfast Habits and Student Achievement in State Elementary School Number 13 Kabila District of Kabila Bone Bolango Regency. The research method is analytic survey with cross-sectional survey design. The population is 102 students enrolled in SDN 13 Kabila.Samples are taken from class III, IV and V, using simple random sampling. Independent variable is breakfast habit and the dependent variable is student achievement in school. Data collection is done by using questionnaire.Data analysis method is